2009
DOI: 10.1160/th09-01-0053
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on risk factors and early outcome of symptomatic distal versus proximal deep vein thrombosis: Results from the OPTIMEV study

Abstract: There is a lack of consensus on the value of detecting and treating symptomatic isolated distal deep-vein thrombosis (DVT) of the lower limbs. In our study, we compared the risk factors and outcomes in patients with isolated symptomatic distal DVT with those with proximal symptomatic DVT. We analysed the data of patients with objectively confirmed symptomatic isolated DVT enrolled in the national (France), multicenter, prospective OPTIMEV study. This sub-study outcomes were recurrent venous thromboembolism, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Use of anticoagulation for 10 or more days was similar (96.8 vs. 97.3 %, p = 0.24) between distal and proximal DVT although patients with distal DVT were less likely to be treated for 3 months (89.1 vs. 91.8 %, p < 0.001) or receive an IVC filter (0.7 vs. 1.8 %, p < 0.001) [ 75 ]. In the OPTIMEV study cohort, patients with distal and proximal DVT suffered recurrent VTE (17 of 787, 2.2 % vs. 15 of 598, 2.5 %) at similar rates (OR 0.8 [0.4–1.8]) [ 76 ]. In a prospective open randomized clinical trial, Lagerstedt et al found that patients with symptomatic distal DVT that received 5 days of heparin only had a much higher rate of progressive/recurrent thrombosis than patients who received heparin followed by 3 months of warfarin (8/28 vs. 0/23, p < 0.01).…”
Section: Guidancementioning
confidence: 99%
“…Use of anticoagulation for 10 or more days was similar (96.8 vs. 97.3 %, p = 0.24) between distal and proximal DVT although patients with distal DVT were less likely to be treated for 3 months (89.1 vs. 91.8 %, p < 0.001) or receive an IVC filter (0.7 vs. 1.8 %, p < 0.001) [ 75 ]. In the OPTIMEV study cohort, patients with distal and proximal DVT suffered recurrent VTE (17 of 787, 2.2 % vs. 15 of 598, 2.5 %) at similar rates (OR 0.8 [0.4–1.8]) [ 76 ]. In a prospective open randomized clinical trial, Lagerstedt et al found that patients with symptomatic distal DVT that received 5 days of heparin only had a much higher rate of progressive/recurrent thrombosis than patients who received heparin followed by 3 months of warfarin (8/28 vs. 0/23, p < 0.01).…”
Section: Guidancementioning
confidence: 99%
“…This is lower than in general orthopaedic surgery where the rate of DVT is reported as 40–60 % [ 23 ], but similar to the incidence of DVT following knee arthroscopy which has been reported as 0.6 % when diagnosed clinically and up to 17.9 % when using radiography [ 31 , 60 ]. The consequences of asymptomatic below knee DVT and the importance of its prevention and treatment remains controversial and a systematic review of the treatment of below knee DVT’s concluded there was insufficient evidence to recommend treatment over mere surveillance [ 8 , 19 , 29 , 34 , 43 , 45 , 58 , 61 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Calf DVTs are the most frequent component of the cluster of VTE events used in previous trials of VTE prophylaxis, yet their detection with CDU is technically challenging and results are inconsistent. The ultrasound technicians and radiographers were mainly blinded in their assessment of our primary outcome.…”
Section: Internal Validitymentioning
confidence: 99%